THE APTIAN STRATIGRAPHY OF SOUTHERN TUARKYR (NW TURKMENISTAN, CENTRAL ASIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
The ammonite successions of Turkmenistan, particularly those of the Greater Balkhan and Tuarkyr areas, are considered references for the Aptian Stage. Six sections across the uppermost Barremian - basal Upper Aptian interval were studied in the Tuarkyr desert in October 1997,and ammonites and bivalves were collected. Data are compared with those from a section sampled by a Russian team in 1959. The stratigraphic distribution of the faunas in the sections is discontinuous, as the fossiliferous levels intercalate with terrigenous sediments. The ammonite faunas, at least in the intervals sampled, show low diversity and are dominated by the genus Deshayesites in the lower Aptian and the genus Epicheloniceras, associated with the less common Caspianites, in the basal upper Aptian. The Turkmenistan sections contain species present also in the Caucasus, England, Germany, France and Switzerland, indicating that the Turkmenian faunas reflect impoverishement rather than geographic isolation. The chronologic equivalence between the Turkmenian Epicheloniceras subnodosocostatum Zone and the Epicheloniceras martinioides Zone in England seems questionable because the Epicheloniceras-bearing beds of the Tuarkyr correspond to the upper part of the E. martinioides Zone, i. e. the Epicheloniceras buxtorfi Subzone. The bivalve fauna consists mainly of pteriids, Exogyrinae oysters and trigoniids. These groups undoubtedly indicate a very shallow, fairly warm and fully marine environment, typical of the Tethyan Lower Cretaceous. The heterodonts are too rare to give further bathymetric indications. None of the taxa indicate deep burrowing and all are assumed to be ?? littoral. The bivalve fauna shows strong affinities with that of the English Lower Greensand.